CASE HISTORY OF OIL AND GAS IN THE CARPATHIAN REGION IN THE POST-WAR PERIOD - Пуйда, Р. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article refers to the training of highly qualified specialists for oil production in the Carpathian region. And also about opening of new deposits of oil and gas in a post-war period.